2010
DOI: 10.31505/rbtcc.v12i1/2.415
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da depressão em pacientes com lesão medular.

Abstract: Estudos contradizem a crença de que toda pessoa com lesão medular sofre de depressão. Para dimensionar o problema e subsidiar intervenções clínicas em contextos de reabilitação, investigouse o nível de depressão por meio do “Inventário Beck de Depressão” em 125 pacientes lesados medulares internados em hospitais de reabilitação; com idade entre 17 e 63 anos. Destes, 36,8% apresentaram depressão moderada a grave e 35,2%, leve a moderada. Não houve diferenças significativas quanto ao nível de depressão, tempo e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 5 publications
1
10
0
3
Order By: Relevance
“…The main causes of SCI shown in the present study were traffic accidents, followed by gunshot wounds. Conceição et al 20 and Custódio et al 21 demonstrated similar results, with the same variables as the main causes. Different data were found by Brito et al 23 that reported falls (42.6%) as the main cause.…”
Section: 33supporting
confidence: 71%
See 2 more Smart Citations
“…The main causes of SCI shown in the present study were traffic accidents, followed by gunshot wounds. Conceição et al 20 and Custódio et al 21 demonstrated similar results, with the same variables as the main causes. Different data were found by Brito et al 23 that reported falls (42.6%) as the main cause.…”
Section: 33supporting
confidence: 71%
“…This can be explained in view of the etiology of traumatic injuries, stemming mainly from the increase in traffic accidents and violence to which young males are more exposed. 4,18,20 In this study as well as in other ones, being married was prevalent among those affected by SCI, 7,24 however, there are other studies that bring us information on single people. 9,15,25 Authors affirm that persons with SCI marry less frequently than the general population and that this may be due to reduction in social contact.…”
Section: 33mentioning
confidence: 71%
See 1 more Smart Citation
“…5 The chronicity generated by the consequences of SCI brings about important social and economic loss, leading to disenchantment of life, loss of labor capacity, partial impossibility of locomotion and leisure, need for adaptation and, in some situations, loss of autonomy, changes in body image and negative feelings between ambiguous fear of permanent disabilities and social exclusion, insecurity, aggression, anxiety, impulsiveness, social isolation, hopelessness, feelings of inferiority, ambivalence, anger, fear and hopelessness. 2,6 The significant changes with respect to morbidity of people bearers of LE, a biological perspective to a psychosocial, as reflection of the social transformations occurred in a given historical and social context. That is the Decade of 1970, the main causes of death of the persons involved from SCI were urinary tract complications, and kidney function, while in the general population predominated the deaths from cardiovascular, renal, respiratory problems, suicide, and neoplasms.…”
Section: -4mentioning
confidence: 99%
“…In the early 1980, occurred relative decrease renal causes deaths and relative increase by suicide, liver disease and alcohol abuse, thus decreasing the biomedical causes and increasing the causes psychosocial in nature. 6 In the face of high rates of consumption of alcoholic beverages on the world stage, it was noted the importance of investigation of alcoholism in artisanal fisherfolk victims of SCI, in order, the damage suffered by them, which is responsible for generating motor disability For data collection, we used a structured script consisting of two parts, namely:…”
Section: -4mentioning
confidence: 99%